Drinking Patterns, Gender and Health III: Avoiding vs. Seeking Healthcare - Green, Carla A. (2010)
BACKGROUND: Inability to predict most health services use and costs using demographics and health status suggests that other factors affect use, including attitudes and practices that influence health and willingness to seek care. Alcohol consumption has generated interest because heavy, chronic consumption causes adverse health consequences, acute consumption increases injury, and moderate drinking is linked to better health while hazardous drinking and alcohol-related problems are stigmatized and may affect willingness to seek care. METHODS: A stratified random sample of health-plan members completed a mail survey, yielding 7884 respondents (2995 male/4889 female). We linked survey data to 24 months of health-plan records to examine relationships between alcohol use, gender, health-related attitudes, practices, health, and service use. In-depth interviews with a stratified 150-respondent subsample explored individuals’ reasons for seeking or avoiding care. RESULTS: Quantitative results suggest health-related practices and attitudes predict subsequent service use. Consistent predictors of care were having quit drinking, current at-risk consumption, cigarette smoking, higher BMI, disliking visiting doctors, and strong religious/spiritual beliefs. Qualitative analyses suggest embarrassment and shame are strong motivators for avoiding care. CONCLUSIONS: Although models included numerous health, functional status, attitudinal and behavioral predictors, variance explained was similar to previous reports, suggesting more complex relationships than expected. Qualitative analyses suggest several potential predictive factors not typically measured in service-use studies: embarrassment and shame, fear, faith that the body will heal, expectations about likelihood of becoming seriously ill, disliking the care process, the need to understand health problems, and the effects of self-assessments of health-related functional limitations.